2018
DOI: 10.1097/md.0000000000012987
|View full text |Cite
|
Sign up to set email alerts
|

Double filtration plasmapheresis in treatment of acute pancreatitis associated with severe hypertriglyceridemia

Abstract: Rationale:Severe hypertriglyceridemia is the 3rd-leading cause of acute pancreatitis. Current treatment option for hypertriglyceridemia associated with acute pancreatitis is mainly supportive measures, including adequate fluid supply, pain management, and broad-spectrum antibiotics if necessary. Extracorporeal method by mean of plasmapheresis is effective in reducing serum level of triglyceride. It has been proposed to have therapeutic potential in limited small sample studies.Patient concerns:A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…The DFPP treatment quickly removes TG‐rich lipoproteins, which theoretically reduces the accumulation of toxic free fatty acid metabolites of TGs and the hyperviscosity caused by chylomicrons. However, a clear benefit of DFPP in reducing the severity and improving outcomes in HTGP has not been conclusively shown 13,26 . In our study, we found that early initiation of DFPP treatment seemed to have no obvious influence on patients’ clinical outcomes.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The DFPP treatment quickly removes TG‐rich lipoproteins, which theoretically reduces the accumulation of toxic free fatty acid metabolites of TGs and the hyperviscosity caused by chylomicrons. However, a clear benefit of DFPP in reducing the severity and improving outcomes in HTGP has not been conclusively shown 13,26 . In our study, we found that early initiation of DFPP treatment seemed to have no obvious influence on patients’ clinical outcomes.…”
Section: Discussioncontrasting
confidence: 59%
“…American Society for Apheresis classes HTGP as a category III indication (the individualized decision is necessary) 12 . To date, the experience of DFPP in HTGP patients is quite limited and mainly based on case reports and small case series 13 . Therefore, we performed this retrospective observational study of HTGP using propensity score matching.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertriglyceridemia is the third most common cause of AP, after gallstones and alcohol, and the causative factor in about 9% of patients [1,3]. It is usually seen in patients whose TG levels exceed 1000 mg/dL [3].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia is the third most common cause of AP, after gallstones and alcohol, and the causative factor in about 9% of patients [1,3]. It is usually seen in patients whose TG levels exceed 1000 mg/dL [3]. Studies estimate that one in five patients with severe hypertriglyceridemia will experience at least one episode of acute pancreatitis [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation